Demographic characteristics, treatment, and outcome of patients with Kaposi sarcoma: Ten‐year follow‐up results of a single center. (15th September 2021) - Güneş, Begüm; Mert, Ömer; Onsun, Nahide
Abstract: Background: Clinical features, types of Kaposi sarcoma, and treatment outcomes have not been well‐defined in Turkey. In this study, we reviewed records of the patients who had been diagnosed with Kaposi sarcoma in the last decade in a single center and evaluated treatment results. Methods: Medical records of the Kaposi sarcoma patients seen in the last decade in a single tertiary center were evaluated in detail. Results: A total of 27 patients were identified; 18 patients had been checked for HHV8; and 16 of those patients were positive for HHV8. One patient was positive for HIV. Two patients having mycosis fungoides and myasthenia graves developed iatrogenic KS after immunosuppressive treatments. Interferon α was used in 21 patients; 8 patients achieved complete response; and 11 patients achieved a partial response. No serious side effects were observed. Systemic involvement did not develop in any patients except lymph node involvement in a patient with widespread skin lesions.